Anatomical Analysis of Transient Potential Vanilloid Receptor 1 (Trpv1+) and Mu-Opioid Receptor (Oprm1+) Co-expression in Rat Dorsal Root Ganglion Neurons - Ma, Wenting; Sapio, Matthew R.; Manalo, Allison P.; Maric, Dragan; Dougherty, Mary Kate; Goto, Taichi; Mannes, Andrew J.; Iadarola, Michael J. (Frontiers in Molecular Neuroscience, 2022)
Primary afferent neurons of the dorsal root ganglia (DRG) transduce peripheral nociceptive signals and transmit them to the spinal cord. These neurons also mediate analgesic control of the nociceptive inputs, particularly through the µ-opioid receptor (encoded by Oprm1). While opioid receptors are found throughout the neuraxis and in the spinal cord tissue itself, intrathecal administration of µ-opioid agonists also acts directly on nociceptive nerve terminals in the dorsal spinal cord resulting in marked analgesia. Additionally, selective chemoaxotomy of cells expressing the TRPV1 channel, a nonselective calcium-permeable ion channel that transduces thermal and inflammatory pain, yields profound pain relief in rats, canines, and humans. However, the relationship between Oprm1 and Trpv1 expressing DRG neurons has not been precisely determined. The present study examines rat DRG neurons using high resolution multiplex fluorescent in situ hybridization to visualize molecular co-expression. Neurons positive for Trpv1 exhibited varying levels of expression for Trpv1 and co-expression of other excitatory and inhibitory ion channels or receptors. A subpopulation of densely labeled Trpv1+ neurons did not co-express Oprm1. In contrast, a population of less densely labeled Trpv1+ neurons did co-express Oprm1. This finding suggests that the medium/low Trpv1 expressing neurons represent a specific set of DRG neurons subserving the opponent processes of both transducing and inhibiting nociceptive inputs. Additionally, the medium/low Trpv1 expressing neurons co-expressed other markers implicated in pathological pain states, such as Trpa1 and Trpm8, which are involved in chemical nociception and cold allodynia, respectively, as well as Scn11a, whose mutations are implicated in familial episodic pain. Conversely, none of the Trpv1+ neurons co-expressed Spp1, which codes for osteopontin, a marker for large diameter proprioceptive neurons, validating that nociception and proprioception are governed by separate neuronal populations. Our findings support the hypothesis that the population of Trpv1 and Oprm1 coexpressing neurons may explain the remarkable efficacy of opioid drugs administered at the level of the DRG-spinal synapse, and that this subpopulation of Trpv1+ neurons is responsible for registering tissue damage.